Efektifitas Maggot Black Soldier Fly terhadap Kualitas Kompos Tahun 2024 - Izati, Meci Miftahi; Afridon, Afridon; Irmawartini, Irmawartini; Darwel, Darwel; Wijayantono, Wijayantono (Jurnal Kesehatan Lingkungan Mandiri, 2024)
Data from the Ministry of Environment and Forestry for 2022 shows that the annual waste generation in Padang City reaches 234 thousand tons. Part of the waste comes from market waste, 15.36%. One way to process organic waste that is environmentally friendly is by bioconversion. The aim of this research is to see the effectiveness of maggots on compost quality. This type of research is a Quasi Experiment (quasi experiment) with the research design being Post Test Only Group. This research was carried out with 3 treatments, namely using black soldier fly maggots 80, 100 and 120 gr and 4 repetitions with the same weight of waste. The results of this research are that compost with 120 gr maggots matures on a day faster than 80 gr and 100 gr maggots, namely on the 15th day with a temperature of 26 °C, humidity 40%, pH 7 and C/N ratio ranging from 14, 88 - 15.49, this is in accordance with SNI 19-7030-2004. Based on analysis using the ANOVA test, it was found that there was a significant difference in the length of composting time and C/N ratio of compost because the p value was <0.05. People should use maggots to process waste and compost and cultivate their own maggots so that they can have economic value.